Application of multi-criteria optimisation in marina planning on the Montenegrin coast - Tomovic Sreten; Sekulic Goran (Polish Maritime Research)
Development of nautical tourism in Montenegro, seen as a potentially profitable industry segment has started twenty years ago. The first steps taken in this direction were defining the legal framework, in particular: Law on Coastal Zone, Tourism Master Plan of Montenegro, Law on Yachts, followed by establishment of supporting organizations - Maritime Safety Department of Montenegro, Port Authorities and Border Police Department. Having invested efforts in adoption of planning documents and enactment of legislation relating to nautical tourism in recent period, Montenegro is seeking to impose itself as an important nautical destination. The first serious step towards achieving this goal was construction of a world-class marina Porto Montenegro in Tivat in 2010. The Special Purpose Spatial Plan for Coastal Zone provides for development of network of marinas to be constructed on the Montenegrin Coast. In the light of this, contribution of this paper is reflected in application of multi-criteria optimization in defining an optimum order of marina construction. The paper defines selection of criterion functions from the aspects of ecology, economy, security, specific aspect and aspect of suitability assessment for the location. The paper also presents the process of defining different criterion weights. The multi-criteria analysis determines a compromise solution for marina planning at Montenegrin Coast, which reconciles conflicting interests. The compromise solution is only a proposal, while a final decision remains with a decision maker.